2021
DOI: 10.1007/s12649-021-01564-1
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production Using Brewery Spent Grain: Optimal Hydrothermolysis, Fermentation of Waste and Role of Microbial Populations

Abstract: The hydrothermolysis variables temperature (150 -210 °C) and time (10 -20 minutes) were assessed to improve hydrolysis e ciency of brewery spent grain (BSG) for renewable energy generation. The intensi cation of the pretreatment was expressed by the severity variation (2.8 -4.5) and the process was optimized with methane production of 411.6 ± 7.2 mL. g -1 STV (severity 4.2). The fermentationmethanogenesis of BSG and hydrolysate resulting from BSG hydrothermolysis process under severity of 4.2 (210 o C for 10 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Sphaerochaeta , 35 Bacteroides 36 and Macellibacteroides are 37 are fermentative microbes that can consume organic compounds such as starch, textile, and protein and produce volatile organic acids, predominantly acetate, formate, and butyrate. The aforementioned taxa have been reported to coexist in anaerobic systems of brewery grain fermentation 38 and raw textile effluent treatment. 39 On the other hand, Prevotella , Caproiciproducens and Ruminiclostridium were found to be beneficial together for the degradation of polysaccharides and protein, such as cellulose and hemicellulose and contribute to the acidification process.…”
Section: Resultsmentioning
confidence: 99%
“…Sphaerochaeta , 35 Bacteroides 36 and Macellibacteroides are 37 are fermentative microbes that can consume organic compounds such as starch, textile, and protein and produce volatile organic acids, predominantly acetate, formate, and butyrate. The aforementioned taxa have been reported to coexist in anaerobic systems of brewery grain fermentation 38 and raw textile effluent treatment. 39 On the other hand, Prevotella , Caproiciproducens and Ruminiclostridium were found to be beneficial together for the degradation of polysaccharides and protein, such as cellulose and hemicellulose and contribute to the acidification process.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, breaking down the spent grains into their constituents will yield a number of value-added components including carbohydrates and proteins, which constitute a suitable medium or substrate for the fermentative production of various bioactive compounds [18]. Consequently, pretreatments will prepare the lignocellulosic substrate for microbial activity, making it more accessible to the microbial consortium [19]. These pretreatments will break cellulose into glucose and hemicellulose into mainly xylose and arabinose, which are the most abundant monosaccharides present in the hydrolyzed spent grains [20].…”
Section: Pretreatment Methods Of Brewers' Spent Grainsmentioning
confidence: 99%
“…A study done by Gomes et al reported that hydrothermolysis led to a 10% increase in methane production from BSG. Particularly, 467.6 NmL/g methane was produced by a pretreated sample (hydrothermolysis at 140 • C for 15 min) compared to 409.8 NmL/g produced by the unpretreated sample [19]. Finally, ultrasonic pretreatment holds potential for large-scale processes.…”
Section: Pretreatment Methods Of Brewers' Spent Grainsmentioning
confidence: 99%
See 1 more Smart Citation
“…84 Hydrothermolysis is performed at 150°C–210 °C for a period (10–20 minutes), which accelerates the rate of OW degradation. 85…”
Section: Pretreatment Of Organic Waste Before Its Conversion Into Bio...mentioning
confidence: 99%